Shape descriptors applied to the analysis of different types of the engineering elements - Đurić, Isidora; Ilić, Vladimir; Ralević , Nebojša (Journal of Production Engineering, 2019)
The aim of this research is to analyse, numerically describe and classify the elements from the image, using the shape descriptors. The paper discusses standard shape descriptors based on discrete moments associated with the certain element shape, as well as their combinations with other global shape descriptors. The new shape-based object analysis approach is illustrated by studying two essentially diverse types of the engineering elements, different by their nature and origin, but similar according to the visual representation of their shape characteristics. The usefulness and efficiency of the considered descriptors in such classification tasks is illustrated by experimental results.